the Persepsi siswa terhadap kebiasaan Sholat Dhuha dan pengaruhnya terhadap kedisiplinan siswa di lingkungan Madrasah Ibtidaiyah - A. FAUZI (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Strengthening students’ discipline character is one of the key objectives of education in Madrasah Ibtidaiyah, which can be developed through the habituation of religious activities such as the Duha prayer. This study aims to examine the relationship between students’ perceptions of the Duha prayer practice and their discipline levels in the Madrasah Ibtidaiyah environment. The research employed a quantitative approach with a correlational ex post facto design. Data were collected through questionnaires and observation. The data analysis used Pearson Product Moment correlation and simple linear regression to determine the relationship and the extent of influence between the variables. The findings indicate a significant relationship between students’ perceptions of the Duha prayer habit and their discipline, with a correlation level ranging from moderate to strong and a meaningful contribution of influence. Therefore, it can be concluded that students’ perceptions of the Duha prayer practice have a positive effect on their discipline in Madrasah Ibtidaiyah.